Pemetaan Klaster Industri Kreatif Kuliner Khas Kalteng Di Kota Palangka Raya Dengan Analisis Kluster Hirarki Sebagai Dasar Penyusunan Kebijakan Optimalisasi Kuliner Lokal - Wahyu Prasetyo; Alexandra Hukom (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research examines the mapping of creative culinary industry clusters typical of Central Kalimantan in Palangka Raya City using Hierarchical Cluster Analysis. The main objective of this research is to identify clustering patterns of the local creative culinary industry which can be the basis for formulating local culinary optimization policies. By applying Hierarchical Cluster Analysis, this research succeeded in uncovering the characteristics and relationships between creative culinary industry players in Palangka Raya, as well as development potential that can be improved through appropriate policies. It is hoped that the results of this research can provide strategic recommendations for local governments and other stakeholders in designing and implementing policies that support the growth of the creative culinary industry, while promoting the richness of Central Kalimantan's unique culinary delights.